Managing Careers / Theory and Practice - Baruch Yehuda (Financial Times - Prentice Hall, 2004)
This book addresses the concepts and principles of career planning and management in a contemporary context. Abbreviations, Preface, Introduction: Career Perspectives, Individual Careers: Career Choice and Career Stages, Individual Careers and Career Models, Organizational Career Systems, The Dynamic Nature of Career Management, Career Management Practices, Global Career Management, Managing Career Diversities, Conclusion: The Future of Career Management, Company Index, Author and Subject Index.